Media Health Literacy on Prevention of Noncommunicable Diseases in Adolescents - Hidayatullaili, Neneng Aprilia; Syamsulhuda Budi Musthofa; Ani Margawati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Health literacy has an important role in health promotion efforts, where literacy focuses on accessing, understanding, assessing, and applying the information obtained so that literacy can have an impact across generations. Health literacy in adolescents is an effort to prevent noncommunicable diseases through behaviors such as eating patterns, smoking, physical activities and others, which are areas that are less explored so it is very important to have an individual approach to healthy behavior. Objective: This study was to examine health literacy in preventing noncommunicable diseases in adolescents. Methods: Systematic review database method used, including Google Scholar, JSTOR, ScienceDirect, Springer Link, PubMed. Inclusion criteria used to select articles include articles using Indonesian and English, year of publication in the 2018-2022 range (last 5 years), full text or non-duplicate and the type of article selected is a research article. Five articles were selected that met the inclusion criteria 1 and 1book as an additional reference. Results: Health literacy can help health promotion efforts to improve individual abilities in accessing, understanding, assessing, and applying information related to the prevention of noncommunicable diseases through various media. So that health literacy in individuals and sources of information has the effect of changing lifestyles and a healthy environment. Conclusion: As a means of preventing noncommunicable diseases in adolescents from a young age, the development of health technology, which is a tool that improves individual abilities to obtain good health outcomes, has contributed to the prevention of noncommunicable diseases at an earlier age.